1987
DOI: 10.1007/bf01885150
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of an unusual foreign body in small bowel

Abstract: The inadvertent ingestion of foreign bodies is an infrequent occurrence in adults. Three cases of an unusual form of foreign body ingestion are reported here. In each case the foreign body recovered was a plastic bag clip, found attached to the small bowel mucosa. The radiographic appearances of this foreign body are demonstrated, and the pathologic findings related to its ingestion are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The radiologist co-author of the present case report (RK) experimented by placing three different plastic clips in the CT scanner in order to determine whether they would give a signal; nothing showed up on the scan. However, Guindi et al assert that in two out of three cases where radiographs were taken, an accumulation of calcium, phosphate and oxalate bile salts on the plastic ties caused them to show up as ‘opaque densities’ in which the tie’s characteristic configuration was identifiable on close inspection 13. Tang et al assert that while conventional radiographs and CT scans revealed small bowel obstruction, the cause could not be identified through either method 14.…”
Section: Discussionmentioning
confidence: 99%
“…The radiologist co-author of the present case report (RK) experimented by placing three different plastic clips in the CT scanner in order to determine whether they would give a signal; nothing showed up on the scan. However, Guindi et al assert that in two out of three cases where radiographs were taken, an accumulation of calcium, phosphate and oxalate bile salts on the plastic ties caused them to show up as ‘opaque densities’ in which the tie’s characteristic configuration was identifiable on close inspection 13. Tang et al assert that while conventional radiographs and CT scans revealed small bowel obstruction, the cause could not be identified through either method 14.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other foreign bodies can become lodged in the distal small inte stine (14)(15)(16). Lar son (17) reported retrieving two wing nut s that were lodged in the ileocecal valve.…”
Section: Discussionmentioning
confidence: 99%
“…Of the people who ingest these clips, a surprisingly large proportion (20%) consists of healthy adult males who allegedly ate their meals too quickly 9,12,14,17,22,25,26,30,31 . That being said, the vast majority of cases are either elderly, edentulous, intoxicated, visually or cognitively impared 11,13,15,19,22–24,32–40 . In the latter cohorts, little can be done to prevent ingestion, instead the focus should be on preventing bowel perforation by modifying the material to one which is safer to ingest.…”
mentioning
confidence: 99%
“…9,12,14,17,22,25,26,30,31 That being said, the vast majority of cases are either elderly, edentulous, intoxicated, visually or cognitively impared. 11,13,15,19,[22][23][24][32][33][34][35][36][37][38][39][40] In the latter cohorts, little can be done to prevent ingestion, instead the focus should be on preventing bowel perforation by modifying the material to one which is safer to ingest.…”
mentioning
confidence: 99%